2012
DOI: 10.24266/0738-2898.30.4.219
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Phosphorus Concentration on Growth of Muhlenbergia capillaris in Flooded and Non-Flooded Conditions

Abstract: Research was conducted to evaluate the effect of phosphorus (P) concentration in irrigation water on growth of a southeastern U.S. native grass Muhlenbergia capillaris in flooded and non-flooded conditions. Plants of Muhlenbergia capillaris (Lam.) Trin. (gulf muhly grass) growing in 3.8 liter (1 gal) containers in 85:15 sand:peat were flooded to the substrate surface for 0 (non-flooded) or 3 days (flooded). Between flooding events, plants were drained for 6 d with no additional irrigation. The flood-drain proc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 13 publications
1
7
0
Order By: Relevance
“…Leachate P was higher in flood treatments than in non-flood treatments. A similar study also found that P concentration in leachate was higher in flooded plants than non-flooded [59]. In non-flood treatments, leachate P was similar regardless of planting combination.…”
Section: The Effects Of Polyculture On Growth and Phosphorus Uptakesupporting
confidence: 55%
See 4 more Smart Citations
“…Leachate P was higher in flood treatments than in non-flood treatments. A similar study also found that P concentration in leachate was higher in flooded plants than non-flooded [59]. In non-flood treatments, leachate P was similar regardless of planting combination.…”
Section: The Effects Of Polyculture On Growth and Phosphorus Uptakesupporting
confidence: 55%
“…Looking beyond these two studies, a third study that used a similar flooding technique and surveyed a native landscape grass, Muhlenberia capillaris (Lam.) Trin., found that SDW and root dry weight (RDW) was higher in non-flooded than flooded treatments (Christian et al, 2012). Comparing the results of the three studies establishes that plant tolerance to short term flooding cannot be assumed based on plant functional group.…”
Section: Flooding and Seasonal Effects On Growthmentioning
confidence: 89%
See 3 more Smart Citations